Musculoskeletal Health in Premature Ovarian Insufficiency. Part One: Muscle - Samad, Navira; Nguyen, Hanh H.; Scott, David; Ebeling, Peter R.; Milat, Frances (Seminars in Reproductive Medicine, 2020)
Accelerated bone loss and muscle decline coexist in women with premature ovarian insufficiency (POI), but there are significant gaps in our understanding of musculoskeletal health in POI. This article is the first of a two-part review which describes estrogen signaling in muscle and its role in musculoskeletal health and disease. Current evidence regarding the utility of available diagnostic tests and therapeutic options is also discussed. A literature review from January 2000 to March 2020 was conducted to identify relevant studies. Women with POI experience significant deterioration in musculoskeletal health due to the loss of protective effects of estrogen. In addition to bone loss, muscle decay and dysfunction is now increasingly recognized. Nevertheless, there is a paucity of validated tools to assess muscle parameters. There is a growing need to acknowledge bone–muscle codependence to design new therapies which target both muscle and bone, resulting in improved physical performance and reduced morbidity and mortality. More high-quality research and international collaborations are needed to address the deficiencies in our understanding and management of musculoskeletal health in women with POI.
Keywords: premature ovarian insufficiency; osteoporosis; bone; muscle; early menopause